Large-Scale Fading and Time Dispersion Parameters of UWB Channel in Underground Mines - Abdellah Chehri; Paul Fortier; Pierre Martin Tardif (International Journal of Antennas and Propagation)
RF channel measurements in underground mines have important applications in the field of mobile communications for improving operational efficiency and worker safety. This paper presents an experimental study of the ultra wideband (UWB) radio channel, based on extensive sounding campaigns covering the underground mine environment. Measurements were carried out in the frequency band of 2–5 GHz. Various communication links were considered including both line-of-sight (LOS) and non-LOS (NLOS) scenarios. In this paper, we are interested in more details of the variations of the RMS delay spread and mean excess delay with Tx/Rx separation, and the variation of RMS with mean excess. The distance dependency of path loss and shadowing fading statistics is also investigated. To give an idea about the behaviour of UWB channel in underground mines, a comparison of our approach with other published works is given including path loss exponent, shadow fading variance, mean excess delay, and RMS delay spread.